Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff